Pseudotumor of the Larynx: A Previously Unreported Side Effect of Apremilast - Eleftherios Ntouniadakis; Fredrik Landström (Karger Publishers, 2020)
Apremilast (Otezla®) is a relatively novel orally administered non-biologic disease-modifying anti-rheumatic drug (DMARD) extensively used in the management of psoriasis and psoriasis arthritis, lately approved for treating oral ulcerations in Behçets disease. Its advantageous side effect profile together with its uncomplicated follow-up and monitoring when compared to other DMARDs facilitates even a broad off-label prescribing. Here, the first case of laryngeal pseudotumor in a patient treated with apremilast for plaque psoriasis is presented.